Addressing the risk of bacterial contamination in platelets: a hospital economic perspective. Issue 10 (13th July 2017) - Li, Justin W.; Brecher, Mark E.; Jacobson, Jessica L.; Harm, Sarah K.; Chen, Dorothy; El‐Gamil, Audrey; Dobson, Al; Mintz, Paul D.
Abstract : BACKGROUND: Bacterially contaminated platelets (PLTs) remain a serious risk. The Food and Drug Administration has issued draft guidance recommending hospitals implement secondary testing or transfuse PLTs that have been treated with pathogen reduction technology (PRT). The cost implications of these approaches are not well understood. STUDY DESIGN AND METHODS: We modeled incurred costs when hospitals acquire, process, and transfuse PLTs that are PRT treated with INTERCEPT (Cerus Corp.) or secondary tested with the PLT PGD Test (Verax Biomedical). RESULTS: Hospitals will spend 221.27 (30.0%) more per PRT‐treated apheresis PLT unit administered compared to a Zika‐tested apheresis PLT unit that is irradiated and PGD tested in hospital. This difference is reflected in PRT PLT units having: 1) a higher hospital purchase price (100.00 additional charge compared to an untreated PLT); 2) lower therapeutic effectiveness than untreated PLTs among hematologic‐oncologic patients, which contributes to additional transfusions (96.05); or 3) fewer PLT storage days, which contributes to higher outdating cost from expired PLTs (67.87). Only a small portion of the incremental costs for PRT‐treated PLTs are offset by costs that may be avoided, including primary bacterial culture, secondary bacterial testing (26.65), hospital irradiation (8.50), Zika testing (4.47), and other costs (3.03). CONCLUSION: The significantly higher cost of PRT‐treated PLTs over PGD‐tested PLTs should interest stakeholders. For hospitals that outdate PLTs, savings associated with expiration extension to 7 days by adding PGD testing will likely be substantially greater than the cost of implementing PGD‐testing. Our findings might usefully inform a hospital's decision to select a particular blood safety approach.